Augmented reality based interior design - Chew, Chai Ying (2022)

(untitled)
This project is about using Augmented Reality (AR) to help visualise a design. AR is a technology that renders virtual objects into the real world captured in device screen in real time. It aims to make users see a virtual object as it is coexisting in the real world environment. An interior designer needs to present the design idea to their clients and get approval. It is convenient to design in 2D floor plan and 3D room, but when it comes to presenting the design, 2D floor plan and 3D room may not give a vivid experience. This may affect the client’s satisfaction Due to not having a real feeling of the design in such a completely virtual environment. Besides, when planning and designing a room, people need to manually measure the room with some tools, such as measuring tape, to get the dimension of the room. Then check with the furniture they see in the store and imagine how they will look and feel when it is put in their room. These problems can be solved by utilising AR technology in interior design. In this project, AR technology is used to measure the dimensions of the room, create a floor plan of the room and display the furniture. Augmented reality technology can help bring virtual furniture into real world environments, it allows furniture to be inserted as actual dimensions in the real world, making furniture appear as if they really exist, and have a lifelike experience. The location of the furniture in the real world will be located and can be viewed again in the same location in the future. Also, not only will the visualisation of the design be enhanced, but 2D floor plans and 3D rooms of the design in AR view will be automatically generated, and design features are also available in these views, making it a more complete interior design application. Besides, the designs can be shared and exported, the furniture used in each room of a house will be summarised into a list to guide users in putting their design into reality.